Adopting modular construction in the Malaysian construction industry / Muhamad Faiz Musa … [et al.] - Musa, Muhamad Faiz; Mohammad, Mohammad Fadhil; Mahbub, Rohana; Yusof, Mohd Reeza (Universiti Teknologi MARA Cawangan Selangor, 2018)
Prefabrication and offsite construction promotes sustainability in the construction environment and industry that is essential to protect ecosystems, improves air quality, reduces waste, conserves natural resources and improves water quality. This paper discusses a study on adopting modular construction through Industrialised Building System (IBS) approach in the Malaysian construction industry. The sustainability principles in offsite construction and IBS have always maintained a balance between environment and construction, improve human self-respect and encourage economic development.